GRAMMATICAL AND LEXICAL IN INFORMAL CONVERSATION OF TEENAGER IN SUKABUMI CITY ON SUNDANESSE MAINTENANCE - Sri Rahayu (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2024)
Indonesia has hundreds of regional languages which are the mother tongue for the society of each region. Sundanese is the second largest language in Indonesia with 32.4 million speakers (Ajeng Wirachmi Litbang MPI Friday, January 21, 2022). Sukabumi cultural observers claim to be concerned about the continuity of adolescent language among adolescents endangered, even though at all levels of education Sundanese learning materials are still scheduled in schools, Sukabumi (Pikiran Rakyat, March 14, 2018) Based on a survey from the author that almost 90% of parents who have teenagers provide Indonesian as a first language for their children. This condition is caused by the position of Indonesian as official language, unity language, national language so that its use is much wider than regional languages. Sundanese language will turn to the minority and it is danger situation if the teenager in kota Sukabumi do not use Sundanesse. The purpose of this study is to find out how grammatical and lexical Sundanese in informal conversations of teenagers in Sukabumi city and know their sika about their regional language. The methodology used in this study is descriptive qualitative by analyzing grammatical and lexical informal adolescent conversation. This study also collected data with a number of questions in the form of questioners on 20 adolescents and 20 parents. The findings in this study revealed that the grammatical that appears in adolescent conversations is the use of Sundanese affixes used in Indonesian and some words in Indonesian influenced by Sundanese phonemes. Lexical that tends to appear are simple verbs, synonym and repetition. The teenager's attitude towards Sundanese revealed that 50% of the teenagers used Sundanese at home, the rest, 48% mixed Indonesian and Sundanese, and only 2% only used Indonesian.